Seed germination of 53 species from the globally critically imperiled pine rockland ecosystem of South Florida, USA: effects of storage, phylogeny and life-history traits. Issue 1 (11th January 2018) - Salazar, Ana; Maschinski, Joyce; Possley, Jennifer; Heineman, Katherine
Abstract: Germination studies at the community level are crucial for understanding and predicting changes in species distribution patterns, particularly in endangered plant communities. We investigated the effects of dry (11–25% relative humidity) and freezing (–18°C) storage conditions, phylogeny and plant life-history traits (life-form, life-span, microhabitat and seed dispersal mode) on seed germination percentage (GP) and time to reach 50% germination ( T 50 ) of 53 species native to pine rocklands in South Florida, USA, a globally critically imperiled ecosystem. Most species we studied (68%) withstood dry and freezing storage conditions and thus e x situ seed banking can assist their long-term conservation. Bayesian mixed effect models revealed that there was a significant phylogenetic signal in GP and T 50 across species. Life-history covariates did not explain significant additional variation in GP in models controlling for the phylogenetic relationships among species. T 50 differed among species with contrasting dispersal modes, with animal-dispersed seeds exhibiting more delayed germination than wind-dispersed or unassisted seeds. Differential germination responses across species with different seed dispersal modes have implications for potential shifts in species composition under disturbance and climate change. Thus, knowledge of species-relatedness and some life-history traits such as seed dispersal mode can significantly assist management decisions regarding seed storage and conservation of subtropical endangered plants.